URGENSI PERAN ORANG TUA DALAM MEMBINA BUDI PEKERTI PADA ANAK (Telaah Surat Luqman Ayat 12-24) - LULUK LUSIANA ARIFA; Eka Susilawati; Moh Faruk; Nurul Laily (STAINU Purworejo, 2022)
The purpose of this research In this study to determine the urgency of the role of parents in fostering character in children. This research method uses a qualitative approach with a descriptive type. The results of this study indicate that parents are mother figures who gave birth to their children and fathers who are of the same birth are most importantly similar to their children both physically and in behavior. And it is parents who have a very important role in shaping the character of children so that they have character, respect each other, be honest, polite, have responsibility, be kind, friendly, and obey the rules. The problem in this study is that parents do not understand the importance of character building for children and assume that character building is only in formal education (schools) and children are not paid enough attention or are not educated optimally so that children have bad characters. Unfavorable characters such as speaking impolitely, lack of care for fellow friends, dishonest with parents and lack of respect for elders. The need for spirituality is the need to maintain faith, restore faith, fulfill religious obligations, and to balance one's intellectual and emotional abilities, so that with this ability will help realize the complete human person. Spiritual intelligence is the main potential that parents must pay attention to so that children experience proper development. Parents often ignore the spiritual development of preschool age children because they think that preschool age is just a playing age so that their spiritual development has not become a priority. Emotional and spiritual intelligence is very important in and for human life. Efforts in developing this intelligence must start from parents, because parents are the first to be recognized by people as a child, parents are the first madrasa for their children.